Postnatal exposure to an acoustically enriched environment alters the morphology of neurons in the adult rat auditory system - Svobodová Burianová, Jana; Syka, Josef (Brain structure & function, 2020)
The structure of neurons in the central auditory system is vulnerable to various kinds of acoustic exposures during the critical postnatal developmental period. Here we explored long-term effects of exposure to an acoustically enriched environment (AEE) during the third and fourth weeks of the postnatal period in rat pups. AEE consisted of a spectrally and temporally modulated sound of moderate intensity, reinforced by a behavioral paradigm. At the age of 3-6 months, a Golgi-Cox staining was used to evaluate the morphology of neurons in the inferior colliculus (IC), the medial geniculate body (MGB), and the auditory cortex (AC). Compared to controls, rats exposed to AEE showed an increased mean dendritic length and volume and the soma surface in the external cortex and the central nucleus of the IC. The spine density increased in both the ventral and dorsal divisions of the MGB. In the AC, the total length and volume of the basal dendritic segments of pyramidal neurons and the number and density of spines on these dendrites increased significantly. No differences were found on apical dendrites. We also found an elevated number of spines and spine density in non-pyramidal neurons. These results show that exposure to AEE during the critical developmental period can induce permanent changes in the structure of neurons in the central auditory system. These changes represent morphological correlates of the functional plasticity, such as an improvement in frequency tuning and synchronization with temporal parameters of acoustical stimuli.
Keywords: Neurons; Rats; Enriched environment; Animals, Newborn; dendrity; neuroplasticita; Auditory Cortex; potkani Long-Evans; metathalamus; Auditory Pathways; Dendritic Spines; Neuronal Plasticity; Critical period; tvar buňky; Inferior Colliculi; novorozená zvířata; krysa rodu Rattus; Rat; Cell Shape; sluchová dráha; zvířata; Acoustic Stimulation; colliculus inferior; dendritické trny; Dendrites; neurony; Spines; Rats, Long-Evans; Geniculate Bodies; Central auditory system; akustická stimulace; sluchové korové centrum; Animals